Implications of Deafblindness: The Physical and Mental Health and Social Trust of Persons with Usher Syndrome Type 3. (July 2016) - Wahlqvist, Moa; Möller, Claes; Möller, Kerstin; Danermark, Berth
Introduction: The aim of this study was to describe health and social trust in persons with Usher syndrome type 3 (USH3) in relation to hearing and visual impairment. Methods: Participants were recruited from the Swedish Usher database. Twenty-one persons with USH3 received two questionnaires, which covered a wide range of domains related to health and social trust. Fifteen individuals, 4 men and 11 women aged 19–71 years, responded. Each outcome measure within every domain reported by the individual was structured into a matrix, which included auditory and visual findings. Results: Severe problems with health and social trust were apparent for persons with USH3. Differences in the number of reported problems were suggested. Three persons had cochlear implants, and they reported far fewer problems with physical health, mental health, and social trust than the others. Discussion: Three major patterns emerged. The first was that the group was heterogeneous with regard to the problems reported in the biopsychosocial dimensions; that is, general health, physical health, and mental health, as well as social trust. The second was that none of the biopsychosocial dimensions could be disregarded when describing health among persons with USH3. The third major pattern was that a cochlear implant might benefit the health of persons with USH3. Implications for practitioners: The results suggested poor physical and mental health and severe social trust problems for people with USH3. Interdisciplinary strategies are required to facilitate the rehabilitation of persons with USH3 throughout their lifespan.